The development and valorizaton of local fodder resources in the governorate of Kebili - Mannai, Amal; Moujahed, Nizar; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2023)
The report highlights a crucial two-day workshop in Kebili, Tunisia, aiming to enhance the utilization of local feed resources, particularly date palm by-products. It addresses key points such as the challenges in Tunisia's livestock feed, the workshop's main goals, specific objectives, and notable outcomes. Additionally, the report explores the diverse audience, participants, partners, and outlines how the workshop was strategically implemented, including a group assessment.